Avaliação da qualidade dos serviços prestados pela direção do Centro de Ciências da Saúde da Universidade Federal de Santa Maria (UFSM) - Dornelles, Murilo da Silva (2016)
This study aimed to evaluate the degree of satisfaction of users of the subunits of the Health Sciences Center of the Federal University of Santa Maria (UFSM). To achieve this objective, an evaluation survey instrument based on the SERVQUAL model was used, in order to assess the quality of services and it was applied to users of services provided by the board of the center. In data analysis, there was a considerably high level of satisfaction perceived by users. In addition, it was found that for most respondents, the working hours of the center were satisfactory and they consider that the board staff treats people politely. It was also pointed out that users agreed that the members of the board demonstrated to have knowledge of the administrative routines of UFSM. On the other hand, it was clear that respondents do not consider that bureaucracy contributes to improve the quality of services and that the center´s management provides individualized services to the subunits. Moreover, it is noteworthy that one of the main weaknesses, which should be given more attention by the managers of the Health Sciences Center, is related to the infrastructure of the unit, since the aspects related to this issue are among the least positively evaluated. The survey also revealed that there was a difference in the evaluation between the gender of the respondents regarding some aspects related to quality and that those teachers who hold management positions, staff with over ten years of experience in UFSM and those with more than three years in the position tended to evaluate more negatively several quality attributes.